Intra and interobserver analysis of the Sanders classification for calcaneal fractures - Costa, Luís Henrique Grassi Marques da; Silva, Thiago Alexandre Alves; Benevides, Wilel de Almeida; Baumfeld, Daniel Soares (Scientific Journal of the Foot & Ankle, 2019)
Objective: To evaluate the intra and interobserver variation in the Sanders classification of calcaneal fractures and the clinical-radiological correlation of postoperative X-ray images and computed tomography (CT) scans. Methods: We sent pre- and postoperative images in the form of a questionnaire to 18 foot and ankle surgeons with varying experience and examined evaluations of the postoperative reduction and Sanders classification quality criteria of 12 calcaneal fractures. The kappa (Ƙ) values were calculated and compared to those in the literature, and the quality of the reduction was compared to the patient's American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Scale (AOFAS-AHS) score. Results: The mean intraobserver Ƙ of the Sanders classification was 0.49. Disregarding the subclasses, the intraobserver Ƙ was 0.55, and when type III and IV fractures were grouped, the intraobserver Ƙ was 0.57. The interobserver Ƙ values in these same three conditions were 0.22, 0.20, and 0.21, respectively. We also observed that the group of less experienced surgeons showed better intraobserver Ƙ values than the more experienced surgeons. In the analysis of the reduction quality based on X-ray images and the AOFAS-AHS score of the patient, we found a value of p=0.043. Conclusion: The Ƙ values were consistent with previous studies, confirming moderate intraobserver reproducibility and acceptable interobserver reliability. We also confirmed the presence of a significant relationship between the reduction quality based on X-ray images and the AOFAS-AHS score of the patient. Level of Evidence III; Diagnostic Studies; Nonconsecutive patients, no uniformly applied reference gold standard.